“Work does change lives”: a qualitative study exploring employment specialists’ perspectives on assisting youth through supported employment in rural Canada - Cassia Warren; Kirsten McCulloch; Jessica Su; Matthew Wenger; Skye Barbic (International Journal of Public Health, 2026)
Objectives To understand the strengths and limitations of implementing supported employment for youth (ages 16–24) in rural northern Canadian communities from the perspective of employment specialists. Methods A purposive sample of 10 employment specialists was recruited from Northern British Columbia and interviewed. The qualitative data were analyzed thematically, guided by reflexive thematic analysis. Results The analysis showed three themes which can be connected to three levels: (1) Societal factors influencing employment outcomes (macro level), (2) Organizational barriers and facilitators (meso level), and (3) Employment specialists’ capabilities (micro level). Conclusion Rural northern communities offer unique strengths (e.g., close-knit social networks, community-driven values) and limitations (e.g., chronic under-resourcing, geographic isolation, access to integrated mental health services). To enhance the success and sustainability of supported employment for youth in rural northern settings, implementation strategies must be tailored to address the intersecting macro (e.g., policy and funding), meso (e.g., organizational capacity), and micro (e.g., individual level) factors that shape program delivery. Strong national and provincial emphasis should be on informing a rural-informed, context-sensitive approach that prioritizes collaboration, long-term investment, and system integration.